Spatial and temporal changes in land and water resources on the northern slopes of the Tianshan mountains from the perspective of “production-living-ecological space” - Xu, Xingang; Tian, Hao; Yang, Guang; Li, Xiaolong; He, Xinlin; Li, Yi; Gao, Yongli; Li, Fadong; Li, Pengfei; Liu, Bing; Xue, Lianqing (Frontiers in Environmental Science, 2023)
The rapidly growing social demand for water and land, along with increasingly constraining economic and social development, have intensified the conflicts between regional production, living, and ecological spaces (PLES). Water and land resources have become major obstacles to long-term growth in arid and semi-arid regions. Therefore, we propose a scenario-based framework for a production, living, and ecological spaces water resource assessment, integrating patch-generating land use simulation (PLUS), Shared Socioeconomic Pathways (SSPs), and multiple regression equations to analye the spatial and temporal variability of these resources on the northern slopes of the Tianshan Mountains (NSTM) and assess the future development of water resources. The results show: 1) from 2000 to 2020, land use types on the northern slopes of the Tianshan Mountains were dominated by ecological land, which decreased to 11,793 km2; production and domestic land use increased. Water for production and ecological use accounted for approximately 93% and a minor proportion of the total water use, respectively. 2) Production land is mainly influenced by population density and Gross Domestic Product (GDP), living land by population density, and ecological land by precipitation and topographic factors. 3) The PLUS model had good applicability, with a kappa coefficient, overall accuracy, and FoM of 0.81, 0.88, and 0.28, respectively. 4) The total water use in the northern slopes of the Tianshan Mountains will increase under all three scenarios between 2030 and 2050, but by varying degrees. Production water use accounts for the most significant proportion (93%), with its use decreasing by 305 million m3 under the SSP3 scenario. Domestic water use shows a slow increase under all three scenarios. Further development of the northern slopes of the Tianshan Mountains should take account of regional ecological vulnerability, and water use for production should be controlled based on existing water resources and ecological capacity to reduce pressure on the environment and provide essential ecological protection and sustainable development.